2015
DOI: 10.1371/journal.pone.0119799
|View full text |Cite|
|
Sign up to set email alerts
|

Genome Based Phylogeny and Comparative Genomic Analysis of Intra-Mammary Pathogenic Escherichia coli

Abstract: Escherichia coli is an important cause of bovine mastitis and can cause both severe inflammation with a short-term transient infection, as well as less severe, but more chronic inflammation and infection persistence. E. coli is a highly diverse organism that has been classified into a number of different pathotypes or pathovars, and mammary pathogenic E. coli (MPEC) has been proposed as a new such pathotype. The purpose of this study was to use genome sequence data derived from both transient and persistent MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 40 publications
(53 reference statements)
3
48
1
Order By: Relevance
“…Richards et al. () noted that the type VI secretion system (T6SS) was present in all four MPEC isolates, compared with a prevalence of 38.6% in non‐mammary isolates of E. coli ( n = 56) and Shigella ( n = 9), and suggested that further research should be conducted into the role of T6SS. This was not supported by comparative genomic analysis of E. coli by Kempf et al.…”
Section: Disease In the Natural Hostmentioning
confidence: 99%
See 3 more Smart Citations
“…Richards et al. () noted that the type VI secretion system (T6SS) was present in all four MPEC isolates, compared with a prevalence of 38.6% in non‐mammary isolates of E. coli ( n = 56) and Shigella ( n = 9), and suggested that further research should be conducted into the role of T6SS. This was not supported by comparative genomic analysis of E. coli by Kempf et al.…”
Section: Disease In the Natural Hostmentioning
confidence: 99%
“…(Wenz et al, 2001). Subclinical and mild clinical manifestations of Klebsiella mastitis also occur quite commonly (Oliveira, Hulland, & Ruegg, 2013;Figure 2 Genomic analysis of mammary pathogenic E. coli (MPEC) suggests that the MPEC phenotype may have arisen from the wider E. coli population on multiple occasions (Richards et al, 2015). Isolates from both transient and persistent E. coli infections are genetically heterogeneous, and there is no consistent genotype or virulence profile associated with either manifestation, making the existence of an MPEC genotype a matter of debate (Dogan et al, 2012;Richards et al, 2015).…”
Section: Gram-negative Mastitismentioning
confidence: 99%
See 2 more Smart Citations
“…The flexible genome consists largely of mobile genetic elements (MGEs), including plasmids, genomic islands (GI), and phages, which facilitate horizontal gene transfer (HGT) and are the driving forces for microbial diversity, evolution, and adaptation potential [21].Despite the proposal of a mammary pathogenic E. coli (MPEC) pathotype [3] and extensive research, no common genetic traits or VFs have been identified for E. coli mastitis isolates, so far [11,[22][23][24]. Recently, several publications analyzed E. coli genomes from intramammary infections, thereby expanding the method spectrum by comparative genomics approaches [25][26][27][28]. All of these studies identified various MPEC genome regions and genes with different 5 of 54 60 65 70 75 80 specificity criteria and significance, many of which are not considered to be classical VFs (or even encode for unknown hypothetical functions), but also genes coding for a type VI secretion system (T6SS), LPS biosynthesis, biofilm association, metabolic functions, and the ferric iron(III)-dicitrate (Fec) uptake system.…”
mentioning
confidence: 99%